The influence of oxygen and pressure on keratinocytes - Adrian Williams; Kawa Ahmad Obeid; Keng Wooi Ng; Wing Man Lau (University of Huddersfield Press, 2019)
This study aims to elucidate the respective effects of normobaric hyperoxygenation and hyperbaric pressurisation on key re-epithelialisation processes in wound healing. Cultured human keratinocytes exposed to intermittent normobaric hyperoxygenation exhibited enhanced cellular migration marked by a significant decline in E-cadherin expression. Keratinocyte proliferation, cellular metabolic activity, as well as IL-6 and IL-8 release were also significantly reduced. These changes were not observed with hyperbaric pressurisation alone. Moreover, cellular differentiation was not altered under normobaric hyperoxygenation or hyperbaric pressurisation. Thus, we conclude that hyperoxygenation differentially modulates key cellular processes in re-epithelialisation .Oxygenation, but not pressurisation, appears to be the predominant factor modulating keratinocyte migration and proliferation. These findings argue for an alternative treatment modality to hyperbaric oxygenation for wound healing, focused on enhancing tissue oxygenation without administering hyperbaric pressures.